Faktor-Faktor Risiko Terjadinya Pneumonia pada Pasien Covid-19 Di RSUP Dr Sardjito Yogyakarta - Perwira, Rendra; Uyun, Yusmein; Widodo, Untung (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2021)
Background: Globally, more than three million confirmed cases of COVID-19 have been reported. According to the WHO report on May 6, 2020, the number of world cases that were confirmed positive was 3 588 773, and the death toll was 247 503 people. Pneumonia appears to be one of the serious manifestations of COVID-19 infection. It is necessary to know the risk factors for COVID-19 pneumonia Methods: The study used a retrospective cohort method, the research subjects were taken from March 2020 to March 2021 with the status of inpatients and confirmed Covid-19 at Dr Sardjito Hospital. Results: In this study, the total sample was 630 patients.The results of the multivariate analysis showed that the factors of age, type II DM, hypertension and male sex were significant for COVID-19 pneumonia. Age 60 years is at risk of pneumonia 1.6 times the risk of developing pneumonia (p=0.041 OR 1.6 95% CI=1.02-2.77), DM Ttype II has a risk of COVID-19 pneumonia 2.48 times (p=0.001 OR 2.48, 95%CI=1.44-4.29), hypertension risk of pneumonia 1.68 times (p=0.042 OR 1.68, 95%CI=1.01-2.77), male gender men were at risk of pneumonia 1.74 times (p=0.004, OR 1.74, 95%CI=1.2-2.57). Conclusion: Age 60 years, hypertension, type II DM and male are significant risk factors for pneumonia in patients with COVID-19 infection.